The Morphological and Anatomical Traits of the Leaf in Representative Vinca Species Observed on Indoor- and Outdoor-Grown Plants - Ciorîță, Alexandra (Plants (Basel), 2021)
Morphological and anatomical traits of the Vinca leaf were examined using microscopy techniques. Outdoor Vinca minor and V. herbacea plants and greenhouse cultivated V. major and V. major var. variegata plants had interspecific variations. All Vinca species leaves are hypostomatic. However, except for V. minor leaf, few stomata were also present on the upper epidermis. V. minor leaf had the highest stomatal index and V. major had the lowest, while the distribution of trichomes on the upper epidermis was species-specific. Differentiated palisade and spongy parenchyma tissues were present in all Vinca species’ leaves. However, V. minor and V. herbacea leaves had a more organized anatomical aspect, compared to V. major and V. major var. variegata leaves. Additionally, as a novelty, the cellular to intercellular space ratio of the Vinca leaf’s mesophyll was revealed herein with the help of computational analysis. Lipid droplets of different sizes and aspects were localized in the spongy parenchyma cells. Ultrastructural characteristics of the cuticle and its epicuticular waxes were described for the first time. Moreover, thick layers of cutin seemed to be characteristic of the outdoor plants only. This could be an adaptation to the unpredictable environmental conditions, but nevertheless, it might influence the chemical composition of plants.